Strategi Permintaan dalam Bahasa Jepang - Astami, Timur Sri (Bina Nusantara University, 2015)
Request strategy in Japanese serves to present desires to hearer and speaker gets benefit from the request. Request strategy consists of bald on record, on record with positive politeness, on record with negative politeness, and off record. Research used qualitative descriptive approach. Data were gathered from Maya Koikeda’s Tokimeki Makkun comic book. Research, in the corpus of data, found bald on record strategy was a strategy without any strings attached. Then, on record with positive politeness was showed by the closeness and solidarity relationship. While on record with negative politeness was showed by minimizing load demand and apology, and off record with a vague ellipsis sentence.